Beta-(1,3/1,6)-D-glucan Helps to Decrease Opportunistic Infections in Crohn's Disease Patients Treated with Biological Therapy - Batovsky Marian; Zamborsky Tomas; Radwan Khaled; Desatova Barbora; Kadleckova Barbora (Archives of Clinical Gastroenterology - Peertechz Publications, 2015)
Background: Secondary intercurrent infections in patients with inflammatory bowel disease (IBD) represent a very important problem in daily clinical practice because of their significant contribution to quality of life and work ability. Beta-glucans are known to act as non-specific immunomodulators that exhibit an anti-inflammatory effect as evident in animal and human studies. Imunoglukan P4H® capsules are nutritional supplement containing 100 mg of beta-(1,3/1,6)-D-glucan pleuran isolated from oyster mushroom Pleurotus ostreatus and 100 mg of vitamin C. Aims: To evaluate the influence of Imunoglukan P4H® (Pleuran, s.r.o., Slovakia) on the secondary morbidity added to biological therapy in maintaining remission of Crohn´s disease (CD) for 12 months. Patients and methods: A double-blinded, placebo-controlled, randomised bicentric study was carried out which included 53 CD patients randomly divided into two groups treated with Imunoglukan P4H® (with beta-(1,3/1,6)-D-glucan pleuran from Pleurotus ostreatus and vitamin C) 1 capsule daily (23 patients) and placebo (vitamin C only) 1 capsule daily (30 patients) respectively. All patients also continued their biological maintenance therapy. Before inclusion the patients were required to: be consented (written), complete a standard quality of life questonnaire for patients with inflammatorybowel disease (SIBDQ), Crohn´s disease activity index (CDAI) was evaluated, full blood count, standard biochemical tests - bilirubine (Bi), alaninaminotranspherase (ALT), aspartataminotranspherase (AST), alcaline phosphatase (ALP), gammaglutamyltranspeptidase (GMT), serum amylases (AMS), natrium (Na), kalium (K), C-reactive proteine (CRP) and faecal calprotectin were also performed. These tests and questionaires were repeated at 2-month intervals, at each time patients reported intercurrent diseases and their lengths. All data were recorded in patient protocol and statistical signification was tested by matching of two ratios with Yates correction and by Mann-Whitney test. Results: From 53 included CD patients 39 reached the end of trial, 14 patients interrupted the study prematurely. Imunoglukan P4H® was administered to 10 patients and placebo to 29 patients. 0/10 patients in Imunoglukan P4H® group (IG) and 1/29 patients in placebo group (PG) interrupted rematurely administration of preparation for intolerance and 1/10 patients in IG and 2/29 patients in PG for relapsing of CD. These differences were not statistically significant (p=0,5519 and 0,7508 resp.). At least one intercurrent infectious or allergic disease occurred in 6/10 of IG patients and in 25/29 of PG patients. In 4/10 respectively 11/29 of patients one intercurrent disease, in 2/10 resp. 7/29 of patients two, in 0/10 resp. 5/29 of patients three and in 0/10 resp. 2/29 of patients four diseases were reported. Imunoglukan P4H® significantly decreased the number of intercurrent diseases compared to placebo in this study (95 % CI, p=0,0196). The treatment did not influence SIBDQ, CDAI, blood count and biochemical parameters tested. Conclusion: Imunoglukan P4H® added to biological therapy in CD patients in remission has significantly reduced the secondary morbidity in comparison to placebo. This preparate was well tolerated, no adverse or undesirable effects were observed and the course of CD remission remained unchanged.